2000
DOI: 10.1007/s100240050022
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Lymphoid Follicles and Aggregates in Gastric Mucosa of Children

Abstract: This study was designed to evaluate the significance of gastric lymphoid follicles (LF) and aggregates (LA) in children with and without Helicobacter pylori (HP) infection. All 605 antrum biopsies performed during 1994 were reviewed and classified according to the presence or absence of inflammation, LF, or LA. HP was searched with a DiffQuik stain in all biopsies showing gastritis, LF, or LA. Gastritis was diagnosed in 80 biopsies (16 with LF, 18 with LA and 46 without LA or LF). Identification of HP in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…9 Reportedly, they do not to occur in normal gastric mucosa 10,11 or are rare. 6,9,12 It was a surprise, then, to find them in the otherwise normal mucosa of patients with gastric stromal sarcomas in the Carney triad (gastric stromal sarcoma, pulmonary chondroma, and extraadrenal paraganglioma) 15 ; they were unexplained.…”
mentioning
confidence: 98%
“…9 Reportedly, they do not to occur in normal gastric mucosa 10,11 or are rare. 6,9,12 It was a surprise, then, to find them in the otherwise normal mucosa of patients with gastric stromal sarcomas in the Carney triad (gastric stromal sarcoma, pulmonary chondroma, and extraadrenal paraganglioma) 15 ; they were unexplained.…”
mentioning
confidence: 98%
“…In immune-mediated colitis, a previous large-scale study including 1074 patients reported the median time of onset of 60 days (interquartile range: 28–88),34 and immune-related hepatitis was reported to occur 3–14 weeks after the introduction of these agents 37. The difference may stem from the fact that lymphoid follicles rarely exist in a normal gastric mucosa,38 and additional insults to the stomach or migration of activated T cells are speculated to be necessary to cause IMG. Comparison of endoscopic and histologic findings before and after initiation of ICIs may be beneficial to prove the hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that lymphoid follicles and / or aggregates are often associated with Helicobacter pylori, but may occasionally be associated with other inflammatory and neoplastic processes (Chakhachiro et al, 2020). Although it is thought that obesity being a low-grade chronic inflammatory condition (Esposito et al, 2003) which may be effective in the formation of lymphoid aggregates, there are also reports that lymphoid clusters that do not contain a germinal center are a normal component of the gastric mucosa without being associated with Helicobacter pylori (Carpentieri et al, 2000).…”
Section: Discussionmentioning
confidence: 99%